Isolation and Characterization of Bacteriophage Targeting E. Coli: A Study on Host Interaction - Raid Ullah,; Khan, Jawad; Ali, Murad; Abbasi, Fariha; Waqar, Amna; Dur-e-Kashaf,; Sajjad, Waseem; Fahim Ullah,; Farooq, Sidra; Zia Ullah, (Indus Journal of Bioscience Research, 2025)
Bacteriophages, viruses that specifically infect bacteria, have emerged as promising alternatives to antibiotics in combating multidrug-resistant bacterial infections. This study focuses on the isolation and characterization of bacteriophages targeting Escherichia coli (E. coli), a pathogen responsible for various infections and a major contributor to antibiotic resistance. The primary objective was to identify and analyze bacteriophages with lytic activity against E. coli, assessing their host interaction dynamics and therapeutic potential. During this study Sewage sample was taken from hospital trash, while clinical samples of E. coli was obtained from the Ayub Teaching Hospital. One new native bacteriophage against E.coli was identified and described, they were assigned the scientific name ECP1. Since ECP1 was able to lyse two out of three but was unable to infect bacteria from other species, it was determined that the phage had a particular host range for E. coli. The separated phage demonstrated viability at pH values between 3 and 9 and up to 50°C. ECP1 demonstrated superior bacterial reduction capabilities by preventing and reducing the initial bacterial inoculum count during 24 hours of observation. ECP1 may be viable options for treating E. coli, given their superior bacterial growth reduction, phage titer, pH, thermal stability, and host range. This study underscores the significance of bacteriophage therapy as a viable strategy to address antibiotic resistance. The findings pave the way for further research into phage-based treatments, offering a sustainable and targeted approach to bacterial infections. Future investigations will focus on optimizing phage formulations and assessing their efficacy in clinical settings.